DETERMINATION OF DEFORMATION CHARACTERISTICS WATER SATURATION AND FLOW OF CLAY SOILS - and (Municipal economy of cities (Technical science), 2013)
The results of deformative and rheological characteristics determination of water-saturated soil under the influence of cyclic load are presented. It is established that more valid findings was obtained from elastic-viscous-plastic modeling of base.